Analysis of Yellow Striped Mutants of Zea mays Reveals Novel Loci Contributing to Iron Deficiency Chlorosis - Chan-Rodriguez, David; Walker, Elsbeth L. (Frontiers in Plant Science, 2018)
The micronutrient iron (Fe) is essential for photosynthesis, respiration, and many other processes, but it is only sparingly soluble in aqueous solution, making adequate acquisition by plants a serious challenge. Fe is a limiting factor for plant growth on approximately 30% of the world’s arable lands. Moreover, Fe deficiency in humans is a global health issue, affecting 1.62 billion people, or about 25% of the world’s population. It is imperative that we gain a better understanding of the mechanisms that plants use to regulate iron homeostasis, since these will be important targets for future biofortification and crop improvement strategies. Grasses and non-grasses have evolved independent mechanisms for primary iron uptake from the soil. The grasses, which include most of the world’s staple grains, have evolved a distinct ‘chelation’ mechanism to acquire iron from the soil. Strong iron chelators called phytosiderophores (PSs) are synthesized by grasses and secreted into the rhizosphere where they bind and solubilize Fe(III). The Fe(III)-PS complex is then taken up into root cells via transporters specific for the Fe(III)-PS complex. In this study, 31 novel, uncharacterized striped maize mutants available through the Maize Genetics Cooperation Stock Center (MGCSC) were analyzed to determine whether their mutant phenotypes are caused by decreased iron. Many of these proved to be either pale yellow or white striped mutants. Complementation tests were performed by crossing the MGCSC mutants to ys1 and ys3 reference mutants. This allowed assignment of 10 ys1 alleles and 4 ys3 alleles among the novel mutants. In addition, four ys∗ mutant lines were identified that are not allelic to either ys1 or ys3. Three of these were characterized as being non-allelic to each other and as having low iron in leaves. These represent new genes involved in iron acquisition by maize, and future cloning of these genes may reveal novel aspects of the grass iron acquisition mechanism.